Prevalence of proximal ascending aorta and target organ damage in hypertensive patients: the multicentric ARGO-SIIA project (Aortic RemodellinG in hypertensiOn of the Italian Society of Hypertension). Issue 1 (January 2019) - Milan, Alberto; Degli Esposti, Daniela; Salvetti, Massimo; Izzo, Raffaele; Moreo, Antonella; Pucci, Giacomo; Bruno, Giulia; Pareo, Ilenia; Parini, Angelo; Paini, Anna; Laurino, Flora I.; Sormani, Paola; et al.
Abstract : Aim: The aim of this study was to assess the prevalence of ascending aortic dilatation and to evaluate the possible association between proximal aorta dilatation and structural or functional markers of cardiac organ damage in hypertensive patients. Background: Dilatation of the sinus of valsalva (SoV) is a common finding in clinical practice and it is associated with an increased cardiovascular risk in hypertensive patients: less is known about the dilatation prevalence of the subsequent portion, the proper ascending aorta and its relationship with cardiovascular organ damage. Methods: This multicentric study included 582 hypertensive and 104 normotensive control individuals. All individuals underwent clinical evaluation and two-dimensional transthoracic echocardiography focused on the evaluation of the aorta. Aortic diameters at three levels were measured: SoV, sinotubular junction and ascending aorta. Results: The prevalence of ascending aorta dilatation was 13%. Patients with ascending aorta dilatation were on average 10 years older than hypertensive patients without aortic dilatation and control individuals. Left ventricular mass was significantly increased ( P < 0.0001) in patients with ascending aorta dilatation with (113.29 ± 3 g/m 2 ) or without (109.16 ± 3 g/m 2 ) SoV dilatation compared with patients with isolated SoV dilatation (98.80 ± 21.8 g/m 2 ) or normal aorta (96.04 ± 26.5 g/m 2 ), with left ventricular hypertrophy (LVH) being twice as common in this group compared with the latter (60 vs. 28%, P < 0.0001). Conclusion: Prevalence of ascending aorta dilatation in hypertensive patients reaches 13%. Hypertensive individuals with enlarged ascending aorta showed significantly increased left ventricular mass, a well known sign of hypertension related cardiac damage and could thus represent a subset of hypertensive patients at an increased cardiovascular risk. Abstract : Supplemental Digital Content is available in the text